Recent Developments in Group I Metabotropic Glutamate Receptor Allosteric Modulators for the Treatment of Psychiatric and Neurological Disorders (2014-May 2015) - Li, Guiying; Jorgensen, Morten; M. Campbell, Brian; Doller, Dario (Current Topics in Medicinal Chemistry, 2016)
In the last 30 years, scientists have made great strides in understanding the biological function of group I metabotropic glutamate receptors (mGlu) in health and disease, as well as developing a broad array of potent and selective agents able to activate or inhibit these receptors. This article provides a comprehensive review of the most recent group I mGlu modulators published in patent and non-patent literatures from 2014 to May, 2015, including design, structure-activity relationship, in silico, in vitro and in vivo properties of key compounds. The current status of clinical mGlu5 negative allosteric modulators (NAMs) and the development of mGlu1 and mGlu5 PET ligands are also highlighted. While the therapeutic potential for group I mGlu modulating agents appears high, significant challenges remain. Strategies to reduce clinical development risks and mitigate important side effects, including psychotomimetic events observed with several mGlu5 NAMs and cellular toxicity associated with mGlu5 positive allosteric modulators (PAMs), while retaining therapeutic efficacy through approaches such as biased ligand signaling are discussed.
Keywords: Metabotropic glutamate receptor 5 (mGlu5)